Effectiveness of predatory bacterium Bdellovibrio bacteriovorus in combination with Pseudomonas fluorescens and Lactobacillus acidophilus as candidates for in vitro anticolibacillosis - Eduardus Bimo Aksono; Muchammad Yunus; Iwan Sahrial Hamid; Gadis Meinar Sari (Open Veterinary Journal)
Background: Bdellovibrio bacteriovorus has stood out since its initial discovery because of its exceptional capacity to feed on other Gram-negative bacteria. Since this specific "predatory bacterium" may be used as both a probiotic and an antibiotic, research on it has expanded in response to the growing issue of AMR. It is necessary to investigate the relationship between B. bacteriovorus and other Gram-negative bacteria, as well as the presence of Gram-positive bacteria, in the same environment to determine whether or not these factors have an impact on their ability as predators.